(Saint – The Tamer of the Wild Beasts. By the Example of the St. Martyr Mina the Miracle-Maker - Луческа, Ели (Poznańskie Studia Slawistyczne, 2021)
The basic and main topic of this research paper is the cult of St. Martyr Mina, especially his ability to tame the wild beasts-the wolves. The starting point of this paper is publication, written by V. Popovska Korobar about the wall paintings from the XV century in the monastery church St. Petka in the village of Brajchino, region of Prespa in Macedonia. In this church the saint is portrayed with some fairly rare iconographic elements that out framed the usual monumental painting of that time – the saint is portrayed as a victorious handler of tamed wild beasts. Popovska Korobar supposes that this kind of interpretation is related with the saint’s life in the desert together with the wild animals, or with the description of the beast in the existing literature about her life in Egypt – the monster with a camel’s head, and she does not identify the species of the animals depicted on the wall of the church. According to our research, this type of iconography is created and based upon the hagiographic texts in combination with the folklore identity of St. Mina and according to that, we think that the wild beasts are tamed wolves.